Reply to "Discussion: The kinetics of blood lactate in boys during and following a single and repeated all-out sprints of cycling are different than in men — Do children indeed release and remove lactate faster than adults?" - Engel, F. A.; Härtel, S.; Sperlich, B.; Holmberg, H. C. (Applied Physiology, Nutrition, and Metabolism, 2015)
It was with interest that we read the comments by Dotan and Falk (2015) concerning our recent publication (Engel et al. 2015) and we appreciate their contributions to this complex aspect of pediatric physiology. These researchers pose important questions regarding the biexponential model we employed to interpret our data and argue for an alternative model on the basis of their own previous findings (Dotan et al. 2003). We would like to respond to their major comments as follows: